Retracted: Studying the impact of the cost-effective Suvidha off-loading dressing in healing neuropathic ulcers in diabetic foot: a case series of 83 cases from South India - Bhat, Sunay N.; Vinoth, D. (International Surgery Journal, 2020)
The article "Studying the impact of the cost-effective Suvidha off-loading dressing in healing neuropathic ulcers in diabetic foot: a case series of 83 cases from South India" is retracted by the Editor-in-Chief, on the request of corresponding author and co-authors. The article is retracted because the authors found some unintended mistakes.